Pengaruh Ekspektasi Guru terhadap Prestasi Belajar Peserta Didik Kelas VI Semester I di Madrasah Ibtidaiyah (MI) Al-Mu’awwanah Jombang - Eliyah Eliyah; Imam Muttaqin; Aslan Aslan (Program Studi PGMI STAI Daruttaqwa Gresik, 2021)
This study aims to dig deep information about the effect of positive and negative teacher expectations on the learning achievement of students in MI. The method used is a survey-associative quantitative research method. The population as well as the research sample was 20 people from the teacher for variable X and 30 students for variable Y. Data analysis was carried out by using multiple regression analysis techniques. From the data analysis conducted, several research findings indicate that positive expectations (X1) and negative expectations (X2) simultaneously do not have a significant effect on student achievement (Y). The strength of the relationship between Variable X1 (Teacher Positive Expectations) and X2 (Teacher Negative Expectations) simultaneously to Y (Student Learning Achievement) is 0.304 = 30.4% with the influence of variable X on Variable Y of 9.3% and 90, 7% is influenced by variables other than the expectation variable. The regression equation that can be formed from the results of data processing is as follows: Y '= 5.310 + 0.006X1 - 0.094X2. From the above equation it can be seen that the effect of positive expectations (X1) on student learning achievement (Y) is positive. This means that if teachers' positive expectations increase, the learning achievement of students will also increase. However, if the positive expectations of the teacher decrease, the learning achievement will also decrease. While the direction of the negative expectation variable (X2) on learning achievement (Y) is negative. That is, if negative expectations increase, learning achievement will decrease. But, on the contrary, if the teacher's negative expectations decrease, the learning achievement of students will increase